Blended Environments: Learning Effectiveness and Student Satisfaction at a Small College in Transition - Gouri Banerjee (Online Learning, 2011)
As higher education moves increasingly to blended and fully online environments, smaller institutions often ask whether this is a desirable trend. They face many challenges in transforming their largely face-to-face didactic teaching traditions to the technology mediated learning environments. Learning effectiveness and student satisfaction are seen to be decisive in whether blended environments are a positive development or not. Using survey data from a liberal arts and sciences institution, we show that student satisfaction with blended learning depends largely on the challenges presented by the subject matter, the degree to which self-directed learning and problem solving are required, and the effectiveness of the chosen pedagogies by which face-to-face and online methods are combined. Blended environments that provide multiple modalities for learning, significant interactivity, familiar technologies, and sustained connections with teachers and peers are preferred by increasing numbers of students in this institution. Although many students and faculty remain skeptical about blended learning, there are others who are very satisfied learners.